Cloud Kitchen Strategy in the Development of Culinary MSMES: the Biscoffery - Karamoy, Gabriella Benedicta (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The food and beverage (F&B) industry in Indonesia has shown rapid growth, particularly among micro, small, and medium enterprises (MSMEs) that have adapted to digitalization and shifting consumer behavior post-COVID-19. This study examines “The Biscoffery,” a dessert-based MSME that successfully transitioned from a home-based pre-order system in Bekasi to a broader Jakarta market through the adoption of cloud kitchen services. Using a qualitative approach with in-depth interviews, the research analyzes business strategies implemented by The Biscoffery, including SWOT analysis, STP (Segmentation, Targeting, Positioning), business model canvas, and the 7Ps marketing mix. The findings highlight how cloud kitchens offer significant advantages in reducing operational costs, enhancing market reach, and streamlining operations compared to traditional storefronts. However, challenges such as dependency on online food delivery platforms and limited customer interaction remain. The study emphasizes the importance of product innovation, effective social media marketing, and branding as critical factors for sustainable business growth. This research provides practical insights for MSMEs aiming to optimize digital-based business models and leverage cloud kitchen services to expand their presence in competitive culinary markets.